2015
DOI: 10.1016/j.fuproc.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fast pyrolysis conditions on yield and structural transformation of biomass chars

Abstract: Fast pyrolysis of biomass (wood, straw, rice husk) and its major components (cellulose, hemicellulose, lignin) was conducted in a wire mesh reactor. The aim of this study was to understand the influence of temperature (350-1400 ∘ C), heating rate (10-3000 ∘ C/s), particle size (0.05-2 mm) and holding time (1-4 s) on the char morphology and char yield. Scanning electron microscopy (SEM) and elemental analysis were conducted to determine the effect of operating conditions on char softening and melting during pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 47 publications
5
75
0
Order By: Relevance
“…This indicates that any differences in biomass composition (cellulose, hemicellulose and lignin) between straw and wood only result in small char yield differences. The char yields of beechwood (rich in Ca, K) and wheat straw (rich in Ca, K, Si) were 4e10% points higher than char yields from pyrolysis of other lignocellulosic materials which was associated with the catalytic effect of alkali metals that affect polymerization/cross-linking [52].…”
Section: Char Yieldmentioning
confidence: 94%
“…This indicates that any differences in biomass composition (cellulose, hemicellulose and lignin) between straw and wood only result in small char yield differences. The char yields of beechwood (rich in Ca, K) and wheat straw (rich in Ca, K, Si) were 4e10% points higher than char yields from pyrolysis of other lignocellulosic materials which was associated with the catalytic effect of alkali metals that affect polymerization/cross-linking [52].…”
Section: Char Yieldmentioning
confidence: 94%
“…The lower char yield at high temperatures may be explained by several factors. Higher heating rates are known to induce lower char yields [18]. Moreover, volatile and char formation are two parallel reactions, and the latter is probably favored at higher temperatures and higher heating rates.…”
Section: Microscopic Analysis Of the Biochar Surfacesmentioning
confidence: 99%
“…Hansen et al [63] reported that the stems of wheat straw contain more lignin and xylan compared to leaves. Trubetskaya et al [64] suggested that at fast heating rates the formation of metaplast is mostly affected by the bond-breaking and cross-linking of organic components present in lignin that are less volatile than holocelluloses.…”
Section: Tablementioning
confidence: 99%